Efektivitas Intervensi Edukasi Perawatan Payudara Dalam Meningkatkan Pengetahuan Dan Keterampilan Ibu Nifas - Mastina, Mastina; Nadya, Embun (-, 2025)
Introduction:The World Health Organization (WHO) and UNICEF consistently recommend exclusive breastfeeding for the first six months of an infant's life, followed by continued breastfeeding and the introduction of adequate complementary foods until the age of two years or beyond. Methods:This community service project aimed to implement and evaluate the effectiveness of an educational intervention on breast care in a community setting. The primary objective was to improve the knowledge and skills of postpartum mothers regarding breast care to prevent breastfeeding complications. The study employed a quasi-experimental design with a one-group pretest-posttest approach. Results: The findings indicate a significant increase in the knowledge of postpartum mothers regarding breast care, with an average score of 89 post-intervention.